Assessments of population exposure to environmental pollutants using air quality measurements during Commonwealth Games-2010. (May 2013) - Chate, Dilip; Beig, G.; Satpute, Trupti; Sahu, Saroj Kumar; Ali, K.; Parkhi, Neha; Ghude, Sachin
Abstract During the "Commonwealth Games" 2010 (CWG-2010) in Delhi, the Indian government has implemented an ambitious project "System of Air quality Forecasting And Research (SAFAR)" for monitoring and forecasting air-quality scenario. Using high-precision spatio-temporal measurements of criteria pollutants from the SAFAR network, the number of cases are estimated for total, cardiovascular and respiratory mortalities and hospital admissions. In a thinly populated airport area, the excess number of cases for total mortality show ∼10 for PM2.5 and 25 for PM10, whereas, ∼110 for PM2.5 and ∼300 for PM10 in most populous Delhi University (DU) area. Cardiovascular mortality in airport area show ∼5 and <10 for PM2.5 and PM10, respectively, but, in DU area show ∼55 for PM2.5 and ∼140 for PM10. In DU locality, respiratory mortality shows ∼7 and ∼20 for PM2.5 and PM10 and, hospital admissions show ∼11 and ∼30 for PM2.5 and PM10, respectively. In airport area, excess cases of respiratory mortality and hospital admission tends to one for exposure to PM2.5 or PM10 levels indicating effective exposure is the key factor for health hazards. As public health gains, low air pollution levels were observed before the CWG due to effective washout by monsoonal rain and during CWG under policy-induced air quality measures could increase the life expectancy as against to post-CWG period. These results are important for the megacities in developing world as the SAFAR project is internationally recognized by the Global Urban Research Meteorology and Environment of the World Meteorological Organization.